2022
DOI: 10.3389/fimmu.2022.840173
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Lipids as Chronic Myeloid Leukemia’s Potential Biomarkers for Disease Progression and Response to Tyrosine Kinase Inhibitors

Abstract: Chronic myelogenous leukemia (CML) is a myeloproliferative neoplasm that expresses the Philadelphia chromosome and constitutively activated Bcr-Abl tyrosine kinase in hematopoietic progenitor cells. Bcr-Abl tyrosine-kinase inhibitors (TKI) do not definitively cure all CML patients. The efficacy of TKI is reduced in CML patients in the blastic phase—the most severe phase of the disease—and resistance to this drug has emerged. There is limited knowledge on the underlying mechanisms of disease progression and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The serum metabolic profile of patients responding and refractory to treatment with tyrosine kinase inhibitors has been assessed and compared. Lipid metabolism has been shown to differ significantly between these groups [26]. Notably higher ceramide and lower sphingomyelin levels were found in the serum of TKI-resistant patients compared to the treatment-resistant group.…”
Section: Metabolomics As An Early Biomarker Of Treatment Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The serum metabolic profile of patients responding and refractory to treatment with tyrosine kinase inhibitors has been assessed and compared. Lipid metabolism has been shown to differ significantly between these groups [26]. Notably higher ceramide and lower sphingomyelin levels were found in the serum of TKI-resistant patients compared to the treatment-resistant group.…”
Section: Metabolomics As An Early Biomarker Of Treatment Resistancementioning
confidence: 99%
“…These scales, in addition to remaining reliable, validated tools for predicting patient outcomes, might also be helpful in individualized, risk-adapted initial treatment decisions and predicting outcomes for appropriate of treatment response. The final section describes the challenges underlying metabolomics-based experiments and discusses the potential pitfalls of the analytical process, including study design and sample collection (Table I [18,19,[21][22][23][24][25][26][27][28]).…”
Section: Metabolomics As a Biomarker Of Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the elevation of ceramide induced apoptosis and rescued sensitivity to TKIs [ 254 ]. The sphingolipidomics profile was also recently analyzed in plasma from patients at different stages of CML, including TKI-resistant patients, and it was found that ceramide levels were increased in TKI-resistant patients while SM and S1P levels were decreased in the chronic- and accelerated-phase CML [ 255 ]. These results seem to be discordant from sphingolipid levels measured in primary cells, particularly in the case of TKI resistance and this might be due to measurements in plasma versus cells [ 254 ].…”
Section: Sls In Hematological Malignanciesmentioning
confidence: 99%